Toward anti-fouling capacitive deionization by using visible-light reduced TiO2/graphene nanocomposites. (22nd September 2015) - Zhang, Wei; Jia, Baoping
Abstract: Abstract : In this work, we showcased a visible-light-assisted reduction of graphene oxide (GO) using N-doped TiO2 photocatalysts. Bench scale capacitive deionization (CDI) experiments determine the optimum working voltage for TiO2 –reduced graphene oxide (RGO) nanocomposites as CDI electrodes at 1.8 V. Furthermore, the coupled TiO2 nanoparticles within the as-prepared composite also exhibited photocatalytic ability by removing the humic acid model pollutant. This property is expected to be beneficial as it could relieve the degree of fouling on the electrosorptive surface caused by dissolved organic compounds. In the end, we have demonstrated their potential as a viable desalination water treatment technology in a pilot scale CDI unit.